A plant virus enhances odorant‐binding protein 5 (OBP5) in the vector whitefly for more actively olfactory orientation to the host plant. Issue 4 (22nd December 2022) - He, Haifang; Li, Jingjing; Zhang, Zelong; Yan, Minghui; Zhang, Beibei; Zhu, Chaoqiang; Yan, Weili; Shi, Baozheng; Wang, Yaxin; Zhao, Chenchen; Yan, Fengming
Abstract: BACKGROUND: The whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) is a notorious agricultural pest and the effective vector of many plant viruses worldwide. Cucurbit chlorotic yellows virus (CCYV), exclusively transmitted by B. tabaci in a semipersistent manner, is a serious causal agent in cucurbit crops in many countries. Plant viruses can manipulate the behaviors of insect vectors to promote the spread of themselves, but underlying mechanisms are remaining unclear. RESULTS: In this study, our observations indicated that B. tabaci, when carrying CCYV, oriented more actively to the host plant cucumber. Transcriptome analysis and quantitative polymerase chain reaction with reverse transcription analysis showed that the odorant‐binding protein 5 ( OBP5 ) was upregulated with viral acquisition. Sequence and phylogenetic analysis showed that BtabOBP5 was highly homologous with nine OBPs from other hemipteran insects. In addition, OBP5 ‐silenced whiteflies significantly altered their orientation behavior towards cucumber plants and towards some typical volatile organic compounds released from cucumbers. CONCLUSION: This study described a novel mechanism by which the olfactory system of vector insects could be regulated by a semipersistent plant virus, thereby affecting insect olfactory behavior and relationship with host plants. These results provided a basis for developing potential olfaction‐based pest management strategies in the future. © 2022 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : The olfactory system of Bemisia tabaci could be hijacked by cucurbit chlorotic yellows virus (CCYV). Odorant‐binding protein 5 ( OBP5 ) was upregulated in viruliferous whiteflies compared with non‐viruliferous whiteflies, leading to more active host localization and more possibility of CCYV transmission.